2015
DOI: 10.3762/bjoc.11.298
|View full text |Cite
|
Sign up to set email alerts
|

Bright molecules for sensing, computing and imaging: a tale of two once-troubled cities

Abstract: SummaryThe circumstances in Colombo, Sri Lanka, and in Belfast, Northern Ireland, which led to a) the generalization of luminescent PET (photoinduced electron transfer) sensing/switching as a design tool, b) the construction of a market-leading blood electrolyte analyzer and c) the invention of molecular logic-based computation as an experimental field, are delineated. Efforts to extend the philosophy of these approaches into issues of small object identification, nanometric mapping, animal visual perception a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 92 publications
0
7
0
Order By: Relevance
“…17,18 Moreover, cation-selective chemosensors have been utilized in developing a supramolecular sensor cassette distributed by OPTI Medical Systems, Inc., which can be used for the detection of Na + , K + , Ca 2+ , CO 2 (indirectly), and pH in untreated whole blood (Figure 1c). 19,20 In this review article, we focus on molecular probe, chemosensor, and nanosensor developments that are either already operational in aqueous environments or that have the potential to be developed into functional chemosensors in aqueous media. We were particularly interested in highlighting literature reports on molecular recognition-based sensing coupled to an optical readout.…”
Section: Introductory Remarksmentioning
confidence: 99%
“…17,18 Moreover, cation-selective chemosensors have been utilized in developing a supramolecular sensor cassette distributed by OPTI Medical Systems, Inc., which can be used for the detection of Na + , K + , Ca 2+ , CO 2 (indirectly), and pH in untreated whole blood (Figure 1c). 19,20 In this review article, we focus on molecular probe, chemosensor, and nanosensor developments that are either already operational in aqueous environments or that have the potential to be developed into functional chemosensors in aqueous media. We were particularly interested in highlighting literature reports on molecular recognition-based sensing coupled to an optical readout.…”
Section: Introductory Remarksmentioning
confidence: 99%
“…In the case of simple organic,o rc oordination compounds, [3] potential "outputs"c an be ac haracteristicc hange in both the absorption or the emission spectra of ac ompound. [4] These have been demonstrated elegantly by de Silva, [5] Andreasson, [6] and Pischel [7] amongsto thers. [8] Through our own work, we have demonstrated that lanthanide (Ln III )c omplexes can be used in solutiona ss ingle MLGMs, [9] sensors [10] and in parallel processes, [11] exploitingt heir characteristic emission properties.…”
mentioning
confidence: 95%
“…13) This phenomenon is exactly related to a “logic gate” concept proposed later by A. P. de Silva. 14) Their solution properties are also interesting. When the methylene spacer -(CH 2 ) n - between the crown ring and ammonium tail group is short, they tend to form low-molar-mass pseudo-cyclic dimers owing to the 1 + 1 intermolecular “tail-biting action”, whereas when it is long enough, they tend to form supramolecular polymers owing to the intermolecular “tail-biting action”.…”
Section: Introduction: How Was the Concept Of “Molecular Machines” Born?mentioning
confidence: 99%